The Effects of Ecological Gamification on Learners’ Engagement - Lucas Fellipe dos Santos (2024)
Personalization of gameful environments such as game-based and gamified learning environments has garnered significant attention in contemporary discourse. Nonetheless, the outcomes remain inconsistent, exhibiting positive, negative, or no effects. At the same time, most of the research has been limited to using traditional gamification strategies (e.g., those involving points, badges, and leaderboards). To tackle this issue, we examined how ecological gamification (i.e., a novelty gamification design strategy based on the gamification elements chance, imposed choice, economy, rarity, and time pressure) influences students’ engagement (i.e., focused attention, perceived usability, aesthetic appeal, and reward), according to their gamification profiles (i.e., Philanthropist, Socializer, Free-spirit, Achiever, Player and Disruptor). A quasi-experimental investiga tion was carried out with 104 participants utilizing a gamified learning platform, with data examined via partial least squares structural equation modeling. Notably, our findings were two folded revealing that i) ecological gamification had a beneficial impact on Disruptors’ perception of usability and ii) enhanced Players’ feelings of being rewarded. Based on the results, we also indicated a series of practical implications and provided various recommendations for future studies. These insights contribute to learning technology and gamified learning, shedding light on the nuanced personalization of gamified educational systems.